Experiment study on thermal behavior of a horizontal high-temperature heat pipe under motion conditions. (January 2022) - Sun, Hao; Liu, Xiao; Liao, Haoyu; Wang, Chenglong; Zhang, Jing; Tian, Wenxi; Qiu, Suizheng; Su, Guanghui
Highlights: The thermal behavior of a horizontal high-temperature heat pipe under motion conditions are experimentally investigated. The motion conditions include transitory inclination, vertical heave, and periodic swing. The impacts of motion types on temperature variation and heat transfer deterioration of heat pipes are summarized. Abstract: High temperature heat pipe is widely applied to multiple industrial fields, including in small modular reactors to cool the reactor core, or as heat exchangers. The thermal behavior of the high temperature heat pipe has been widely researched by theoretical and experimental approaches, including designing, manufacture, numerical analysis, and experimental test on its thermal characteristics of start-up process and operation. As the heat pipe has a potential application protest on mobile nuclear reactors, this paper carried out experimental study on the thermal behavior of the high temperature heat pipe under various motion conditions. The temperature distributions on the heat pipe surface under transitory inclination, vertical heave, and periodic swing, are measured to evaluate the impact of motion conditions on the heat transfer of heat pipe at horizontal position. The transitory inclination causes an obvious temperature variation at both evaporator and condenser. The vertical heave, of which the motion direction is perpendicular to the heat pipe, has negligible impact on the isothermality of the heat pipe. The periodic swing leads to periodic temperature fluctuation, of which the amplitude increase with the decease of the period time. Besides, the dry out phenomenon is easier to happen at the evaporator when the condenser is longer. This paper summarizes the impact of different motion types on the thermal behavior of a horizontal heat pipe and provides a reference for the design and application of the high temperature heat pipe used in nuclear reactors.